Potential of engineered biomedia for the innovative purification of contaminated river water. Issue 51 (1st November 2016) - Sidek, L.; Mohiyaden, H.A.; Lee, L.K.; Foo, K.Y.
Abstract: The performance of a laboratory scale bioreactor was investigated for the biological pretreatment of contaminated river water over the operation period of 6 months. The biofilters were constructed as four identical 5.75 L tanks filled with different carrier supports. The physiochemical properties of the biomedia, including the specific surface area, void fraction, adsorption of methylene blue, and morphological characteristics were examined. The biofilters responded effectively for chemical oxygen demand, biological oxygen demand, ammonical nitrogen, and total suspended solids removal, reaching the maximum removal of 94, 88, 85, and 98%, respectively. The variation of morphological development and biofilm densities revealed the existence of different growth rates and microbial activities under different biomedia supports. The operation is significantly correlated to the unique features of the biomedia. These new engineered structural biomedia are expected to be a potential option to govern the successful water purification process under steady and transient state operations.